The Effect of Applying Blended Learning Using Interactive Writing on Learning Interest and Indonesian Writing Skills in Writing - Khaerunnisa Nurdin; Sulfasyah Sulfasyah; Rosmini Madeamin (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study deals with the effect of blended learning using interactive writing on learning to write simple Indonesian essays on interests and writing skills. This study aims to determine the influence of the application of good learning methods by teachers and students after their application in the learning process. This research method uses a quantitative research design Quasi-Experimental Design with the Nonquivalent Control Group Design type. The population in this study were all 123 class III students. The subjects in this study were students of class III D at SD Telkom Makassar. The data collection technique was filling out a student response questionnaire and written test. The data analysis technique used is quantitative data analysis techniques. The results of the analysis of the description of the interest of the experimental class (III D) students obtained by the researcher showed an increase in student interest after the application of blended learning using interactive writing in a very good category, while for the control class (III B) the results of the analysis of the description of student interest showed an increase but still in the poor category. The results of the description of the writing skills of the experimental class students showed a significant increase after the application of blended learning using interactive writing. There was no significant difference between the students' writing skills in the control class at the pre-test and post-test. The results showed that it was based on multivariate and manova tests. So the application of blended learning using interactive writing affects students' interest and writing skills.